Pengaruh Kompetensi dan Disiplin terhadap Kinerja Pegawai Dimediasi Motivasi pada Kantor Kesyahbandaran dan Otoritas Pelabuhan Kelas IV Muara Sabak - Erizon, Tommi; Suryani, Arna; Sudirman, Sudirman (J-MAS (Jurnal Manajemen dan Sains), 2024)
This study aims to determine and describe the picture of competence, discipline, motivation and performance of employees at the Port Master and Port Authority Office Class IV Muara Sabak and to determine and analyze the influence of competence and discipline on employee performance mediated by motivation at the Port Master and Port Authority Office Class IV Muara Sabak. The type of research uses descriptive verification research. The object of this study is the Port Authority Office and Class IV Muara Sabak Port Authority. This study uses the PLS analysis method. Based on the results of the study, competence has a positive and significant effect on motivation, discipline has a positive and significant effect on motivation, competence has a positive and significant effect on employee performance, discipline has a positive and significant effect on employee performance, motivation has a positive and significant effect on employee performance, competence has a positive and significant effect on employee performance and discipline has a positive and significant effect on employee performance mediated by motivation at the Port Authority Office and Class IV Muara Sabak Port Authority.